PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI ADMIN PADA PT AMOS INDAH INDONESIA JAKARTA UTARA - Krisnawati Gea; Mitri Nelsi (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of leadership style and work motivation simultaneously on the performance of PT employees. Amos Indah Indonesia Jakarta Utara, both partially and simultaneously. This type of research is quantitative research. 2. In this research, the sampling method used was a saturated sample. The object of this research is the admin employees of PT Amos Indah Indonesia Jakarta Utara. So the sample in this research is permanent employees of PT Amos Indah Indonesia Jakarta Utara numbers 85 people. 1. Based on the results of the correlation coefficient analysis (r) in the table above, the correlation coefficient R value is 0.715, where this value is in the interval 0.600 – 0.799, meaning that the Leadership Style variable has a strong level of relationship to Employee Performance. Based on the test results in the table above, an R Square value of 0.512 is obtained, so it can be concluded that the Leadership Style variable has an influence on the Employee Performance variable by 51.2% while the remainder is (100 - 51.2%) = 48.8% influenced by factors. others that were not carried out in this study. Based on the results of the first hypothesis test, the calculated t value > t table or 9.323 > 1.98896 is strengthened by the Sig value. < 0.05 or 0.000 < 0.05 then H0 is rejected and H1 is accepted, so it can be concluded that partially the Leadership Style variable has a significant influence on Employee Performance at PT Amos Indah Indonesia Jakarta Utara. Based on the results of the second hypothesis test, the calculated t value > t table or 7.404 > 1.98896 is strengthened by the Sig value. < 0.05 or 0.000 < 0.05 then H0 is rejected and H2 is accepted, so it can be concluded that partially the Motivation variable has a significant influence on Employee Performance at PT Amos Indah Indonesia Jakarta Utara. Based on the results of the third hypothesis test, the value Fcount > Ftable or 64.242 > 3.11 is confirmed by the ρ value < Sig. 0.05 or 0.000 < 0.05 then H0 is rejected and H3 is accepted, so it can be concluded that simultaneously the Leadership Style and Motivation variables have a significant influence on Employee Performance at PT Amos Indah Indonesia Jakarta Utara